+0  
 
0
36
2
avatar+1436 

Let  \(f(x)=log (x^2-2x)\) and  \(g(x) = \frac{x}{x-1}\). Which expression represents \(f(g(x)\) ?

 

a)  \(log (\frac{x^3 -2x^2}{x-1})\)

 

b) \(log(\frac{x^2-2x(x-1)}{(x-1)^2})\)

 

c) \(\frac{log(x^2-2x)}{log(x^2-2x)-1}\)

 

d)  \(\frac{xlog(x^2-2x)}{x-1}\)

 Apr 30, 2021
 #1
avatar+118611 
+1

f(g (x) )  =  log  [ (x)^2 / ( x - 1)^2  -  2x / (x - 1)   ]   =

 

          x^2 - 2x ( x - 1)                  

log     ____________     =  "b"             

            (x - 1)^2   

 

 

cool cool cool

 Apr 30, 2021
 #2
avatar
0

Thank you so much!

Guest Apr 30, 2021

22 Online Users

avatar
avatar
avatar